2019
DOI: 10.1186/s12934-019-1155-4
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of vacuolar protein sorting components of the HOPS complex leads to enhanced secretion of recombinant proteins in Pichia pastoris

Abstract: Background The yeast Pichia pastoris is a widely used host for the secretion of heterologous proteins. Despite being an efficient producer, we observed previously that certain recombinant proteins were mistargeted to the vacuole on their route to secretion. Simultaneous disruption of one vacuolar sorting pathway together with vacuolar proteases prevented this mis-sorting and resulted in higher levels of secreted heterologous protein. Inspired by the positive results, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…reported that disruption of the autophagy-related Cvt pathway genes ATG8 and ATG11 did not affect the secretion of heterologous proteins in P . pastoris [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that disruption of the autophagy-related Cvt pathway genes ATG8 and ATG11 did not affect the secretion of heterologous proteins in P . pastoris [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report found that deletion of YPT7 increased secretion of the model proteins HyHEL-Fab and CES in the yeast P . pastoris [ 47 ], and of model proteins cellulase (Ctcel8A) and exocellulase (PCX) in S . cerevisiae [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…3, the specific fluorescence was on average 2.5-fold increased in the presence of the proteasome inhibitor (3 vs 8 FU.g DCW −1 after 32 h, and 55 vs 23 FU.g DCW −1 after 48 h). This highlighted that some CalB was lost due to intracellular degradation either in the cytosol 32 or in vacuoles 33,34 prior to secretion, thus explaining the low lipase titer observed in the culture supernatant of P. pastoris strain RIY311, despite higher expression levels of CalB than in Y. lipolytica strain RIY368.…”
Section: Calb Expression Level the Expression Level Of The Calb Genementioning
confidence: 99%
“…Elevated upregulation of the endoplasmic reticulum associated protein degradation (ERAD) pathway may have resulted in rapid degradation of the accumulated product. However, this is rather improbable since the upregulation of this pathway is mostly expected in the first phase of production (Aw and Polizzi 2013;Marsalek et al 2019;Vogl et al 2014). The more probable explanation is partial translational arrest, as previously described by Edwards-Jones et al (2015).…”
Section: Discussionmentioning
confidence: 90%